Characterization of PepB, a group B streptococcal oligopeptidase. - Lin, B (1996)
Group B streptococci were recently reported to possess a cell-associated collagenase. Although the enzyme hydrolyzed the synthetic collagen-like substrate N-(3-[2-furyl]acryloyl)-Leu-Gly-Pro-Ala, we found that neither the highly purified enzyme nor crude group B streptococcal cell lysate solubilized a film of reconstituted rat tail collagen, an activity regarded as obligatory for a true collagenase. We cloned and sequenced the gene for the enzyme (pepB). The deduced amino acid sequence showed 66.4% identity to the PepF oligopeptidase from Lactococcus lactis, a member of the M3 or thimet family of zinc metallopeptidases. The group B streptococcal enzyme also showed oligopeptidase activity and degraded a variety of small bioactive peptides, including bradykinin, neurotensin, and peptide fragments of substance P and adrenocorticotropin.